ANALYSIS OF SOURCES AND USE OF WORKING CAPITAL IN SAVING AND LOAN COOPERATIVE OF MARGA MULIA, BILA VILLAGE, LALA BATA SUB-DISTRICT - Hasriadi, Hasriadi (Universitas Islam Negeri Alauddin Makassar, 2019)
This study aims find out the source and use of working capital as well as find out capital management at the Marga Mulia Savings and Loan Cooperatives Bila Village, Lalabata Sub-District, Soppeng Regency. Research/data collection methods used are through interviews, observations, questionnaires and documentation with data analysis using descriptive data and statistical analysis. In this period (2008-2009), this cooperative had a large source of capital and the use of small working capital so that the profits or rest of the business results in the Marga Mulia Savings and Credit Cooperatives in the current period amounted to Rp. 398,728,620. Period 2009-2010, rest of the business results amounting to Rp. 437,961,520. So the 2008-2010 period of the Savings and Loan Marga Mulia Cooperative can be said to have increased or rest of the business results increased. If the Savings and Loan Cooperative Marga Mulia will maintain and always experience an increase in the rest of the business results, it will last a long time in the field of cooperative business